(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract : Food and nutritional security are the major challenges in 21 centuary world. Many plants growing wild have potential to contribute to sustainable food systems under climate change. In such scenario the food and nutritional insecurity, it is important to introduce new agriculture techniques and search for alternative food and feed ingredients. Some wild root and tuber crops can be used as nutritional food due to its high calorific value and superior carbohydrate content along with minerals and vitamins. Yam (Dioscorea spp.) provides food and medicines to millions of people in the world especially in the tropics and sub tropics. Yams are considered as food famine and plays important role in food needs of small and marginal tribal families during the food scarcity periods. These species are unique for their food, medicinal and economic values but their wider utilization is limited due to the presence of anti-nutritional compositions in some species. The present paper reviews nutritional status and neutraceutical uses of Dioscorea oppositifolia L.